Fungal Skin Diseases and Associated Factors in Outpatients of Bangabandhu Memorial Hospital, Chattogram - Ahmed, Shalahuddin (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2024)
Background: Fungi are ubiquitous in nature and exist as free living saprobes that derive no obvious benefits from parasitizing human. Fungal infection or mycosis is a disease caused by fungi. The prime objective was to determine the prevalence of the fungal skin diseases and explore the associate factors including socio-economic status, demographical and personal hygiene of the patients. Materials and methods: This cross sectional research study was performed in the Outpatients Department of Dermatology and Venereology, Bangabandhu Memorial Hospital, Chattogram during the period from January 2023 to April 2023 (120 days). A total number of 200 patients were randomly selected. Results : Among 200 patients, 75 patients had fungal infection with highest prevalence (37.50%) where ringworm 58(77.33%) and oral candidiasis 3(4.00%) where highest and lowest. In case of associate factors, summer season (60.00%) married (77.67%) secondary education (36.00%) Tk 15000/- Tk-20,000/- monthly (37.33%) and upper middle class status (37.33%) Muslims (86.67%) Traders (32.00%) Urban areas (70.66%) tap water (69.33%) recurrent infections (62.66%) and Overcrowding family (66.66%) had higher prevalence of fungal infections of skin. Conclusion: This study provides a fair picture of fungal skin diseases, better health education, properly maintain personal hygiene, improvement of standard of living, proper case diagnosis and proper treatment and management may remain of importance in managing fungal skin diseases. Chatt Maa Shi Hosp Med Coll J; Vol.22 (2); July 2023; Page 51-55